1993
DOI: 10.1177/0741713693044001002
|View full text |Cite
|
Sign up to set email alerts
|

"Happy Consciousness": Ideology and Hidden Curricula In Literacy Education

Abstract: The content of five widely-used ABE reading series was analyzed 13 years ago by Gerald Coles (1977). Coles found racism, sexism, and socioeconomic stereotypes to "abound" in these materials. Using the same categories of racism, sexism, and the socioeconomic categories employed by Coles, this investigation reconstructed the Coles study to determine if hidden curricula still exist and, if so, to what extent. Findings indicate that today's most popular reading texts have improved since 1977, but only slightly. Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…He concluded that adult basic education texts reinforce the status quo and promote conformity and passivity amongst a learning population that is disproportionately composed of poor and marginalized individuals. Quigley and Holsinger (1993) replicated Coles's methodology, and concluded that racism, sexism, and classism still characterized adult basic education texts in the early 1990s. They argued that while "content has moved from what we today would consider "blatant" sexism, racism, and socio-economic depictions" (p. 28), a hidden curriculum of white, male dominance still existed.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…He concluded that adult basic education texts reinforce the status quo and promote conformity and passivity amongst a learning population that is disproportionately composed of poor and marginalized individuals. Quigley and Holsinger (1993) replicated Coles's methodology, and concluded that racism, sexism, and classism still characterized adult basic education texts in the early 1990s. They argued that while "content has moved from what we today would consider "blatant" sexism, racism, and socio-economic depictions" (p. 28), a hidden curriculum of white, male dominance still existed.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Research focused on adult basic education has argued that hidden curricula support the reproduction of inequality. Coles (1977) and Quigley and Holsinger (1993) analyzed widely used basic education texts whose ostensible curriculum was to teach adults how to read. Both studies found hidden curricula of racism, sexism, and ideologies supportive of social class exploitation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Related research has been conducted in adult literacy classrooms, especially with regard to exploring the ideological content of formal curriculum texts (Coles 1977, Auerbach and Burgess 1985, Lankshear 1987, Quigley and Holsinger 1993. Adult educators and sociologists have also examined the role of literacy and welfare policy in maintaining or reproducing social inequalities (Sheared 1998), most recently with regard to the trend to connect education with workforce preparation (Sparks 1999, St Clair 2000.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…Zacharakis-Jutz and Dirkx (1993) state, for instance, that while 'the issue of workplace literacy has come to occupy a prominent position within the larger educational discourse at both the federal and state levels', except for a 'few noteworthy studies, critical debate and discussion over the nature of these politics, programs, and curricula have been virtually nonexistent ' (1993: 92). With the exception of a few studies (Coles 1977, Auerbach and Burgess 1985, Lankshear 1993, Quigley and Holsinger 1993, Quigley 1997, researchers have not addressed the mechanisms through which power operates at the micro level of the classroom, especially as these mechanisms are played out in the social relations of the classroom (Cervero et al 2001). The purpose of this study, therefore, was to explore how ideologies about work and education are enacted and negotiated in the day-to-day classroom life of educational programmes for welfare recipients.…”
mentioning
confidence: 98%
“…For example, Quigley and Holsinger (1993) show how favorite adult basic-education texts contain a hidden curriculum promoting "individualism and problem solving in isolation" (p. 26). This message diverts literacy students' attention away from possible systemic explanations of problems (as demonstrated by sexist, racist, and classist stereotypes within the same texts) and community problem solving.…”
Section: Knowledge and Learningmentioning
confidence: 99%